Isotopic Discrimination Factors (Δ13C and Δ15N) between Tissues and Diet of the Broad-Snouted Caiman (Caiman latirostris) - Marques, Thiago S; Bassetti, Luis A. B; Lara, Neliton R. F; Araújo, Márcio S; Piña, Carlos I; Camargo, Plínio B; Verdade, Luciano M (Journal of herpetology, 2014)
Natural variation in stable isotope ratios is a useful tool in diet studies. However, the correct interpretation of isotopic data is reliant on proper estimates of discrimination factors. This study aimed to describe the magnitude of the discrimination factors of carbon and nitrogen isotopes between diet and tissues (Δ13Ctissue-diet and Δ15Ntissue-diet) of the Broad-snouted Caiman (Caiman latirostris) and to verify potential differences between age classes. The isotopic ratios of carbon and nitrogen (δ13C and δ15N) were determined in samples of two tissue types (claw and scute) collected from 18 captive animals and in 15 samples of their diet. The Δ13Ctissue-diet was 1.2 ± 0.1 ‰ for claw and 0.9 ± 0.2‰ for scutes; the Δ15Ntissue-diet was 1.1 ± 0.1‰ for claw and 0.8 ± 0.2‰ for scutes. These values were much lower than the values assumed commonly in ecological studies (3–5‰), and similar to a previous study with crocodilians. Our results emphasize the need to determine discrimination factors specific to taxa instead of assuming average values derived from the literature.